2019
DOI: 10.1038/s41559-019-0860-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for increased hominid diversity in the Early to Middle Pleistocene of Indonesia

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 64 publications
2
66
0
1
Order By: Relevance
“…= 10). Furthermore, it should be noted that our Meganthropus sample is represented by Trinil 11620 and Trinil 11621, specimens with controversial affinities and that have been previously attributed to other taxa (see above, and Zanolli et al, ). Additional details of the fossil specimens used in this study are provided in Table S1.…”
Section: Methodsmentioning
confidence: 86%
See 4 more Smart Citations
“…= 10). Furthermore, it should be noted that our Meganthropus sample is represented by Trinil 11620 and Trinil 11621, specimens with controversial affinities and that have been previously attributed to other taxa (see above, and Zanolli et al, ). Additional details of the fossil specimens used in this study are provided in Table S1.…”
Section: Methodsmentioning
confidence: 86%
“…Previous studies of tooth microstructure and dental tissue proportions have identified additional dental features that differ between pongines and hominins, such as the equal reduction of enamel and dentine in Pongo , but preferential loss of dentine in Homo during the process of tooth size reduction in these two groups (Grine & Franzen, ; Smith et al, ; with the exception of Neanderthals, see Olejniczak, Smith, Feeney, et al, ). Pongo molars also differ from those of humans in having lower dentine horns and an overall different shape of the EDJ with broader crowns, broad, and shallow dentinal intercuspal furrow pattern and less medially placed lingual dentine tips (Olejniczak, Martin, & Ulhaas, ; Olejniczak, Smith, Wang, et al, ; Smith et al, ; Zanolli et al, ). In addition, when only fossil individuals were considered, Smith et al () found that enamel has a more uniform distribution across the enamel cap in fossil Pongo than in H. erectus , although relative enamel thickness values overlap substantially in the two taxa (Smith et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations